Bacteria-based immune therapies for cancer treatment. (November 2022) - Howell, Lars M.; Forbes, Neil S.
Abstract: Engineered bacterial therapies that target the tumor immune landscape offer a new class of cancer immunotherapy. Salmonella enterica and Listeria monocytogenes are two species of bacteria that have been engineered to specifically target tumors and serve as delivery vessels for immunotherapies. Therapeutic bacteria have been engineered to deliver cytokines, gene silencing shRNA, and tumor associated antigens that increase immune activation. Bacterial therapies stimulate both the innate and adaptive immune system, change the immune dynamics of the tumor microenvironment, and offer unique strategies for targeting tumors. Bacteria have innate adjuvant properties, which enable both the delivered molecules and the bacteria themselves to stimulate immune responses. Bacterial immunotherapies that deliver cytokines and tumor-associated antigens have demonstrated clinical efficacy. Harnessing the diverse set of mechanisms that Salmonella and Listeria use to alter the tumor-immune landscape has the potential to generate many new and effective immunotherapies.